Visible Light‐Induced Copper‐Catalyzed C—H Arylation of Benzoxazoles†. Issue 11 (1st August 2020) - Ma, Xiaodong; Zhang, Guozhu
Summary of main observation and conclusion: A general method for visible light‐induced copper‐catalyzed arylation of sp 2 C—H bonds of azoles has been developed. The method employs aryl halide as the coupling partner, lithium alkoxide as base. A variety of azoles including benzooxazole and benzothiazole can be arylated. Furthermore, electron‐poor heterocycles such as thiophene possessing one electron‐withdrawing group can also be arylated. Abstract : A general method for visible light‐induced copper‐catalyzed arylation of sp 2 C—H bonds of azoles has been developed. The method employs aryl halide as the coupling partner, lithium alkoxide as base. A variety of azoles including benzoxazole and benzothiazole can be arylated. Furthermore, electron‐poor heterocycles such as thiophene possessing one electron‐withdrawing group can also be arylated.